The Impact of Motivation and Work Discipline on Employee Performance - Zaeni, Nurhaeda; Walda, Walda; Ayu, Mita (Advances: Jurnal Ekonomi & Bisnis, 2023)
This study's objective was to examine and determine the impact of work motivation and work discipline on employee performance at PT. PLN (Persero) Transmission Implementation Unit (UPT) MAKASSAR. This study's demographic consisted of 50 employees from PT PLN (PERSERO) Transmission Implementation Unit (UPT) MAKASSAR. Using census sampling, all populations are represented in the sample. The data source is primary data obtained from respondents' responses to questionnaires. The data analysis method entails descriptive statistical analysis, validity tests, normality tests, reliability tests, multicollinearity tests, heteroscedasticity tests, autocorrelation tests, hypothesis testing via multiple linear regression analysis, t-tests, f-tests, and determination coefficient tests. This study's findings indicate that work motivation positively and statistically significantly influences employee performance. While the work discipline variable has a positive but insignificant effect on employee performance, this study demonstrates that work motivation and work discipline together significantly impact employee performance. The results of this study show conclusively that the positive relationship between work motivation and work discipline on employee performance is a crucial factor in achieving company success, as employees who are motivated and disciplined at work tend to contribute more significantly to achieving company objectives.